Community Preferences to Perform Marriages at Home After The Issuance of Government Regulation No. 48 Of 2014 - Yusefri, Yusefri; Wihidayati, Sri (AJIS: Academic Journal of Islamic Studies, 2024)
The Government Regulation No. 48 of 2014 concerning Tariffs for Non-Tax State Revenues that apply to the Ministry of Religion, among others, stipulates that the cost of registering marriages performed at the religious affairs office (RAO) on working days and hours is zero rupiah (free), whereas if a married is performed at home, it is subject to a fee of IDR 600,000. In fact, many people still perform marriages at home. Against this phenomenon, there are two interesting problems to study. First, how is public knowledge about the Government Regulation No. 48 of 2014? Second, what are the reasons beyond people's preferences for marriages at home instead of at RAO? This study belonged to empirical socio-legal research in the form of field research and applied a qualitative descriptive analysis method. The conclusion of this study fell into two. First, there were still many people who did not know and understood the Government Regulation No. 48 of 2014. The things that underlined people's preferences for marriages at home entailed views and beliefs of the marriage sacredness, tradition or custom, self-respect, avoiding negative images, limited RAO’s facilities, convenience, the distance of RAO, and time efficiency.